Guidelines for Development of Teachers for the 21st Century Learning Management of Schools under Mahasarakham Provincial Administrative Organization: Guidelines for Development of Teachers for the 21st Century Learning Management of Schools under Mahasarakham Provincial Administrative Organization - Laoseenart, Napatchaya; Namwan, Tharinthorn (RATANABUTH JOURNAL, 2024)
The objectives of this research were to: Study the current conditions, desirable condition, need assessment and guidelines for development of teachers for the 21st century learning management of schools under Mahasarakham provincial administrative organization. The research was divided into four phases as follow; phase 1; study the current conditions, desirable condition and need assessment of developing teacher in learning management for 21st century. The research sample consists of 39 school administrators and 166 teachers. The research instrument was questionnaire for study the current conditions, desirable condition for development of teachers for the 21st century learning management. phase 2; study the guidelines for development of teachers for the 21st century learning management. The key informants group include 6 school administrators and teachers in school was best practices of learning management and 9 experts for assess suitability possibility of guideline. The research instrument were interview form, Data were analyzed by content analysis and assessment form of guidelines, Data were analyzed by the mean and standard deviation. The results found that: 1. The current state in overall was high average and the desirable state in overall was in the highest level. The need assessment rank from high to low level was 1) Assessment for learning 2) Child-centered learning 3) Cooperative Learning 4) Technology base Learning. 2. The development guidelines of teacher in learning management for 21st century consist of 19 guidelines as follows: 1) Assessment for learning, 3 guidelines 2) Child-centered learning, 5 guidelines 3) Cooperative Learning, 5 guidelines 4) Technology base Learning, 6 guidelines. The evaluation of guidelines, feasibility and utility was the highest in overall.